Secondary bacterial isolates from previously untreated Buruli ulcer lesions and their antibiotic susceptibility patterns in Southern Nigeria - Moses Chibueze Anyim; Anthony Obiamaka Meka; Joseph Ngozi Chukwu; Charles Chukwunalu Nwafor; Daniel Chukwunweolu Oshi; Nelson Okechukwu Madichie; Ngozi Ekeke; Chukwuka Alphonsus; Obinna Mbah; Chinenye Nwaekpe; Martin Njoku; Dare Fakiyesi; et al. (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Mycolactones, secreted by Mycobacterium ulcerans, were previously believed to prevent super infection in Buruli ulcer lesions. However, little is known about secondary bacterial infections in these lesions. This study evaluated contaminating bacterial flora and their antibiotic susceptibility patterns in cases of previously untreated Buruli ulcer disease from three states in Southern Nigeria. METHODS A prospective analysis was conducted between January and June of 2015 using wound swabs from eligible patients with Buruli ulcer disease, confirmed by quantitative-polymerase chain reaction, with active ulcers. Microbiological analyses including isolation of bacteria, species identification of isolates, and drug susceptibility tests were performed. RESULTS Of 51 patients, 27 (52.9%) were female. One or more bacterial species of clinical importance was isolated from each patient. A total of 17 different microbial species were isolated; 76.4% were Gram-negative and 23.6% were Gram-positive isolates. The most common bacterial species detected was Staphylococcus aureus (24%), followed by Aeromonas hydrophila (13%), Pseudomonas aeruginosa (13%), and Klebsiella pneumoniae (11%). Drug susceptibility tests showed a particularly high frequency of resistance to commonly used antimicrobials in Nigeria for Staphylococcus aureus. CONCLUSIONS Super bacterial infections occur in Buruli ulcer lesions in Nigeria, and these infections are associated with high rates of resistance to commonly used antibiotics in the country.